Extracts of Scrophularia frigida Boiss display potent antitumor effects in human breast cancer cells by inducing apoptosis and inhibition of expression of the human epidermal growth factor receptor 2 - Goldar, S; Baradaran, B; Shekari Khaniani, M; Azadmehr, A; Derakhshan, S M; Mohammadi, A; Mansoori, B; Khaze, V; Shanehbandi, D; Mohammadnejad, L; Baghbani, E (Cellular and Molecular Biology, 2016)
Some species of the Scrophularia genus have been extensively used as a natural remedy for treatment of various medical conditions. The objective of this study was to evaluate the growth inhibitory activity of Scrophularia frigida Boiss extracts as well as to study the effect of the potent extracts on the induction of apoptosis and cell cycle arrest on human breast cancer cells. S. frigida Boiss extracts exhibited obvious inhibitory effects on the growth of cancer cells and induced apoptosis. It is suggested that the extracts exert their anti-proliferative effect through multiple implications such as suppressing growth, arresting the cell cycle, increased DNA fragmentation, downregulation of the expression of human epidermal growth factor receptor 2 and myeloid cell Leukemia-1, and upregulation of pro-apoptotic messenger RNAs like caspase-3 and caspase-9. Taken together, the results obtained indicate that S. frigida Boiss extracts may contain effective compounds that can be used as a therapeutic anticancer agent.